1995
DOI: 10.1108/01443579510099779
|View full text |Cite
|
Sign up to set email alerts
|

Use of simulation in the design of a JIT system

Abstract: Abundant literature is available on the application of simulation in solving layout, materials handling, and production control problems, both in traditional and JIT environments. Senko and Suskind [1] have applied simulation in warehouse designs. Watford and Greene[2] reported on the use of simulation to determine minimum storage facility requirements and the length of time for materials to move between terminals. Pulat and Pulat[3] described a handling capacity study of an automated storage and retrieval sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Lean operations/manufacturing Dov (1992) Food Batch CS Billesbach (1994) Textile Batch CS Ezingeard and Race (1995) Chemical Batch SIM, CS Welgama and Mills (1995) Pharmaceutical Batch CS Iijima, Komatsu, and Katoh (1996) Food Continuous CM, AR, CS Cook and Rogowski (1996) Chemical Continuous CS Gilmore and Smith (1996) Pharmaceutical Batch AR, CS Jones, Hines, and Rich (1997) Brewing Batch AR, CS Mileham et al (1999) Plastic Batch AR, CS Radnor (2000) Chemical also indicated in the literature that in recent times, use of VSM has been increased in process industries to implement lean (Abdulmalek and Rajgopal 2007;Seth, Seth, and Goel 2008;Jimenez et al 2011;Perez et al 2010;Upadhye, Deshmukh, and Garg 2010;Chowdary and George 2012). Literature also implies that quick changeover techniques are often implemented in batch process industries.…”
Section: Type Of Studymentioning
confidence: 99%
“…Lean operations/manufacturing Dov (1992) Food Batch CS Billesbach (1994) Textile Batch CS Ezingeard and Race (1995) Chemical Batch SIM, CS Welgama and Mills (1995) Pharmaceutical Batch CS Iijima, Komatsu, and Katoh (1996) Food Continuous CM, AR, CS Cook and Rogowski (1996) Chemical Continuous CS Gilmore and Smith (1996) Pharmaceutical Batch AR, CS Jones, Hines, and Rich (1997) Brewing Batch AR, CS Mileham et al (1999) Plastic Batch AR, CS Radnor (2000) Chemical also indicated in the literature that in recent times, use of VSM has been increased in process industries to implement lean (Abdulmalek and Rajgopal 2007;Seth, Seth, and Goel 2008;Jimenez et al 2011;Perez et al 2010;Upadhye, Deshmukh, and Garg 2010;Chowdary and George 2012). Literature also implies that quick changeover techniques are often implemented in batch process industries.…”
Section: Type Of Studymentioning
confidence: 99%
“…In the early days, DES was used to pre-test flow layouts in fully automated manufacturing systems (Wu and Wysk, 1989) or in a low-volume, mixed model Just-in-Time assembly system (Carlson and Yao, 1992). Welgama and Mills (1995) used a simulation approach to address design problems faced by a chemical organisation, changing from a traditional to a Just-in-Time system, considering alternative designs for the Just-in-Time system. DES is widely used and an increasingly popular method for studying the design and operations of manufacturing systems (Rabelo et al, 2005;Detty and Yingling, 2000;Kleijnen, 1995).…”
Section: Discrete Event Simulation (Des)mentioning
confidence: 99%
“…Detty and Yingling [12] demonstrated the use of discrete event simulation as a tool to assist organizations with the decision to implement lean manufacturing by quantifying the operational benefits achieved from applying lean principles. Other simulation studies were also conducted to investigate the impact of Just in Time (JIT) and Pull lean principles on improving manufacturing system operational performance [13,14]. Lian and Van Landeghem [15] combined simulation and value stream mapping together with existing data bases of production to develop a tool for assessing lean implementation.…”
Section: Literature Reviewmentioning
confidence: 99%